Oddziaływanie europejskiej unii walutowej na spójność gospodarczą i społeczną Unii Europejskiej - Borowiec, Jan (The Influence of European Monetary Union on the EU's Economic and Social Cohesion, 2006)
The main goal of this issue was the evaluation of potential and real (but in a very limited range) influence of European Monetary union on the EU's economic and social cohesion. On the basis of different empirical research, completed with author's own researches, the influence of currency on real convergence processes were evaluated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 44-55